World production and quality of cow's milk - Petar Bosnić (Mljekarstvo)
World milk production has a great economical effect being in the function of human food production and nutrition. Milk is obtained from cows, buffalos, sheeps, goats, camels and donkey with cow's milk production dominating. The world milk production in 2000 was 568.480 thousands of tons of all types of milk of which 484.895 thousands tons are cow's milk with a total of 85.30 % of the world milk production. Buffalo's milk production is on the second place with 61.913 thousands of tonnes (10.89 %) production capacity. On the three continents (Europe, North America and Asia) 81.82 % of total cow's milk production is located. Developed countries produce 50 % of total milk production, while higher milk production is forecast for the developing countries. The EU countries participate with 23.72 % in the world milk production and with 55.60 % on the European area. High annual lactation production, under selected cow's milk production, of above 6000 kg is located in developed countries, where annual participation of Israel accounts for over 10000 kg of milk per cow. Commercial milk production of genetics cattle accounts from 80 % to 85 %. Milk quality, with regard to milk fat and proteincontent, in developed countries is above an average value. With the annual milk production of 7000 kg of cow's milk, up to 294 kg of milk fat and 238 kg of protein are produced. Due to milk characteristics as agro-food product, milk and dairy products manufacture and transportation are in details regulated with existing quality standards. 95 % of the EU milk producers fulfil international hygienic rules on milk safety standards (somatic cells, microorganisms). With regard to long term development, until 2030, changes on herd management (outdoor and indoor exposure), between continents, will occur. In 2030, the world milk production is forecast to increase by 64%, with cow's milk production of 765.9 million tonnes.